Cuarenta aǫs de la Sociedad Española de Bioquímica y Biología Molecular (1963-2003) / director Emilio Muǫz ; editores María Jesús Santesmases, Ana Romero y Jesús Ávila - Muǫz, Emilio (1937-) Santesmases, María JesúsRomero de Pablos, AnaÁvila, Jesús (Ávila de Grado)
Índice onomástico: p. 351-362